Faculty gender equity indicators 2021: data report - Curtis, John W., author (Colorado State University. Libraries, 2021)
Update and expansion of a 2006 report. A comprehensive tabulation of national data on academic employment by gender from 1995-2019 in the form of four equity indicators: employment status, both by institutional category and full- or part-time status; tenure status; achievement of full professor rank; and salary for full-time faculty members.
ZIP file includes XLSX spreadsheets.
Keywords: academic employment; faculty; diversity; race; gender; equity